VÝZNAM A ZAVÁDZANIE VERNOSTNÝCH PROGRAMOV V PODMIENKACH POSKYTOVATEĽA UNIVERZÁLNEJ POŠTOVEJ SLUŽBY (Perner's Contacts, 2007)
The aim of this article is the solution of loyalty program for selected clients of the universal postal service provider - Slovenská pošta, a.s.. Its major role is to support customers´ loyalty and to prevent them from preferring competitors´ services. Another task is to provide them an above standard treatment in form of additional services, according to the target group.
Keywords: Loyalty program; Customers´ loyalty; CRM